Journalistic quality in Cuba from perception of Villa Clara reporters: ideology and discourse (Islas, 2024)
Introduction: The research analyzes the strategy of ideological polarization in the oral discourse of Villa Clara journalists regarding the Cuban press system.Methods: Methodologies from Discourse Analysis and Ethnography are employed.Results: It is recognized that, for Villa Clara reporters, the ingroup consists of efficient and ethical Cuban journalists, and the public, while the outgroup comprises state actors who hinder professional practice.Conclusions: The strategy of polarization by Villa Clara journalists mitigates the responsibility of the guild for the deficiencies of Cuban journalism and emphasizes the mediation of managers and training centers in the lack of quality and preparation of reporters.
Keywords: ideological polarization strategy; journalistic quality; oral discourse; Cuban journalists; mass media system